Diversity of Wild Vegetables Based on Species and Use Values in Nepal (SAARC Journal of Agriculture, 2026)
Forests are a vital source for diverse vegetables, particularly wild and non-cultivated varieties. The study assessed species richness, status, use values and availability across Nepal using focus group discussions in 30 districts (7 provinces) and key informant surveys in 11 districts. Species distribution was grouped at 500-meter altitude intervals. A total of 334 species of wild and non-cultivated vegetables, belonging to 99 families, were recorded. Bagamati reported the highest species number (174), followed by Lumbini (167), with maximum richness at 501–1000 m altitude (216 species). The availability of vegetables was high in summer and was the highest in the month of June. Among the total species, 276 were consumed fresh and 116 species were leafy vegetables. Widely and commonly used, as well as economically important vegetable species are Kaali niuro (Tectaria coadunata), Paani niuro (Diplazium esculentum), Guchchi chyaau (Morchella esculenta), Bhudki chyaau (Scleroderma citrinum), Taamaa (Dendrocalamus strictus), Khole saag (Nasturtium officinale), Thotne (Aconogonum molle), Koiraalo (Bauhinia variegata), Sisnu (Urtica dioica), Kaande lunde (Amaranthus spinosus), Bethe (Chenopodium album), etc. On the other hand, Tusaa (Arundinaria maling), Main kaandaa (Catunaregam spinosa), Chhatre niuro (Cyathea spinulosa), Ruwaa saag (Megacarpaea polyandra), Baahkaane (Clerodendrum cochinchinense), Sipligaan (Crateva religiosa), Chiniyaa (Macropanax dispermus), etc. are highly localized and rare vegetable species. These species support indigenous and rural livelihoods and therefore require in-situ conservation and domestication for food, nutrition and health security.SAARC J. Agric., 23(2): 173-190 (2025)